A Comparative Study on Promotional Strategies of Two Nepali Telecom Companies, NTC and Ncell - Pokharel, Prakash (KMC Research Journal, 2022)
This paper is intended to compare the promotional strategies of two leading telecommunication industry of Nepal – NTC and Ncell. Telecommunication industry is vital for economic growth. It begins with analyzing and comparing their promotional activities. Then it compares the promotional strategies in two ways: in terms of frequency and in terms of budget they spend. Through comparison, it reveals that promotional activities have been taken very seriously by the Ncell than Nepal Telecom. On the basis of David Aakar model of brand equity, this paper also analyzes the effect of promotional activities into brand equity in the following ways: brand loyalty, brand awareness, perceived quality and brand association of telecommunication companies. It shows that two companies have difference in promotional strategies mainly because of their attitude to be a leader in market.